Association of Oxidative Stress Markers with Atherogenic Index of Plasma in Adult Sickle Cell Nephropathy - M. A. Emokpae; P. O. Uadia (Anemia)
This paper evaluates the association of oxidative stress and atherogenic index of plasma in order to assess the cardiovascular risk in Sickle cell nephropathy especially as lipoprotein levels are lower in SCD than non-SCD patients. Antioxidant enzymes, malondialdehyde(MDA), urea, creatinine, and glomerular filtration rate were evaluated in 110 confirmed sickle cell disease patients: 65 males in steady state, aged 21.1±6.0 years, 30 males with macroalbuminuria, aged 24.5±7.0, years and 15 with chronic kidney disease (CKD), aged 31.8±2.0 years. The mean activity levels of glutathione peroxidase (GPx), superoxide dismutase (Cu/ZnSOD), and catalase (CAT) were significantly lower (P<0.001) in SCD with macroalbuminuria and CKD while MDA was higher (P<0.001) in SCD with macroalbuminuria and CKD compared with controls. There was negative correlation between GPx (P<0.001), Cu/ZnSOD (P<0.02), and Atherogenic index of plasma in SCD with CKD, while MDA shows a positive correlation (P<0.001) with AIP in SCD with CKD. There was however no correlation between CAT and AIP. Decreased activity levels of antioxidant enzymes and low HDL-cholesterol concentration were confirmed in adult SCD with CKD in Nigerians. The increase oxidative stress and high atherogenic index in CKD may accelerate the process of cardiovascular complications in adult SCD patients. Atherogenic index of plasma was negatively correlated with antioxidant enzymes and positively with MDA.